Clima de ondas em uma praia estuarina na Zona Costeira Amazônica - PERREIRA, Jackelynne Mafra (2020)
The wind wave regime is responsible for sediment rework and morphological variation of the coastal zone, being important for the economic activities developed in these environments. This study was carried out in the Pará river estuary, which has an important socioeconomic and environmental role, as part of the OCA project - Amazon Coast Observatory - which aims to implement an observation system for monitoring meteoroceanographic parameters in the Amazon Coastal Zone (ZCA), based on monthly measurements during the dry, rainy and seasonal periods. intermediate over a year. The characteristic seasonality of this region is divided into seasons: rainy (December to May), less rainy (June to November) and the months of January and June may present transitional behavior. During the study period the presence of La Niña of moderate intensity was identified, which increases the intensity of winds and rains in northern Brazil. The collections were made at Vai-Quem-Quer beach, on the island of Cotijuba, located on the right bank of the Pará river estuary. Thus, two collection points were defined, based on local morphology and logistics, the first for the installation. from the meteoceanographic station, and the second to the pressure sensor base. The wave data were obtained from September (2017) to July (2018), and the wind data from September (2017) to May (2018). The processing and analysis of wave and wind data were performed in a Matlab environment. defining the parameters of significant height, maximum height, significant period, energy, power and wave level, and wind intensity, speed and direction. The study showed that the largest waves occur in October, dry period, with wind speed of 11m / s and wave height of 0.97m. For the rainy season, in May the wind presented a speed of 9m / s and a wavelength of 0.45m. The significant period of waves ranged from 0 to 10 s, or characterized as vague waves of gravity. In addition to the wind regime, the waves at the study site are influenced by morphological factors such as the presence of a sandy bar that occurs during the dry season, and meteoceanographic parameters, according to the influence of the ITCZ on the region. Maximum energy and power values occur during the dry period, in accordance with a significant wave height. It is essential to emphasize that the study contributes to a greater knowledge about local hydrodynamics, which is still scarce but of potential importance for coastal management, development of projects of economic value and coastal zone management.